Feeding behaviour and diet choices of cattle with physical and temporal constraints on forage accessibility: an indoor experiment - Ginane, C; Petit, M (Animal science (Penicuik, Scotland), 2005)
An indoor choice experiment was conducted to assess the extent to which heifers offered two forages of different quality will attempt to consume the better quality forage when the weight/number of constraints applied on its harvesting increase. The experiment involved six Salers heifers, a leafy (L) and a coarse (C) hay, and two combined or single accessibility constraints. A physical constraint consisted of reducing the prehensibility of L by covering the trough with a steel grid of either 4 cm or 6 cm mesh size (L4 or L6 v. Linfinity for no grid). A temporal constraint limited the daily access time to both hays to 4 v. 24 h. The hays were either offered alone or together over 2-week periods. Dry-matter intake and feeding time were recorded daily. As expected, the physical constraint (only L4 was efficient) made the heifers decrease their choice (proportion of feeding time or intake) for L regardless of access time, whereas the temporal constraint had no significant effect on choice. The heifers greatly modulated their intake rate of L even under strong physical constraint (L4), and then unexpectedly managed to ingest L faster than C. This emphasizes their motivation to keep ingesting the better quality forage, and underlines the difficulties in comparing diet choices with the optimal foraging theory predictions based on the relative values of a behavioural component subject to large variation, i.e. intake rate. In a very constraining situation (L4 and 4-h access), heifers made a choice that allowed them to increase their total daily digestible organic matter (DOM) intake compared with L4 or C offered alone because of an inverse relationship between feeding time and intake rate on L4. They did not however maximize their total daily DOM intake in a less constraining situation (Linfinity or L6 and C, with 4-h access), since they did not consume L exclusively and showed a marked preference for a mixed diet.